(untitled) (International Journal of Engineering and Computer Science, 2018)
The growth of technology to exchange information in the field of computer network like Internet, mobile communication has been increased and for exchange of information between two users Internet is used as the main source and this exchange of information is not safe which has led to many serious problems such as hacking and duplications. Consequently it is important to give a security of data.